Factors Affecting the Competitiveness of the Seaport: A Case Study in Ho Chi Minh City, Vietnam (Global Journal of Management and Business Research, 2024)
This study uses primary data from a survey of 370 observations in Ho Chi Minh City Vietnam and adopts the Exploratory Factor Analysis Confirmatory Factor Analysis CFA and Linear Regression Modeling LRM with Bootstrap analysis for a reliable test of LRM Its result shows that factors affecting Seaport competitiveness included Geographical Location Connectivity Information Technology Facilities Reputation and Port authority
Keywords: exploratory factor analysis; confirmatory factor analysis; bootstrap; seaport competitiveness; ho chi minh city; vietnam